LEGAL REGULATION OF ELECTRONIC MONEY IN INTERNATIONAL MONETARY LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The subject of the analysis in this paper is the examination of the legalregulation of electronic money in international monetary law. In thiscontext, the first part of the paper points to the influence of electronicmedia on the development of international monetary law, which is todaymost evident in the emergence of electronic money that redefinestraditional money functions. The author therefore deals with theargumentative search for a potential answer to the question of whetherthe role of the issuer of electronic money should be found in the centralbank, the government, the banking system or an international monetarylegal entity such as International Monetary Fund, which operates outsidethe framework of the national monetary jurisdiction in view of theextraterritorial effects of using such money in the financial market. Infurther text, attention is paid to the advantages and disadvantages of theuse of electronic money in commercial transport, the redefinition of statenominalism (lex monetae) and a different understanding of monetaryaggregates. The author conclude that international monetary legislator isexpected to solve the problem of discrepancy between the globalizedfinancial market, on the one hand, and the fragmentation of the monetarysystem, on the other hand (which not include monetary union withcentralized monetary policy) in the future period.